Gross motor developmental dysfunctional outcomes in infantile and toddler pediatric intensive care unit survivors - Chun-Feng Yang; Yang Xue; Jun-Yan Feng; Fei-Yong Jia; Yu Zhang; Yu-Mei Li (BMC, 2019)
Abstract Background Increasing studies have focused on motor function/dysfunction in PICU survivors; however, most studies have focused on adults and older children. This study investigated gross motor developmental function outcomes in infantile and toddler pediatric intensive care unit (PICU) survivors and the factors associated with gross motor developmental functions. Methods This observational study was conducted in the PICU of the First Hospital of Jilin University between January 2019 and March 2019. Thirty-five eligible patients were divided into the dysfunctional (n = 24) or non-dysfunctional (n = 11) group according to the results of the Peabody Developmental Motor Scales, Second Edition (PDMS-2). Baseline gross motor function for all participants before PICU admission was measured via the Age and Stages Questionnaires, Third Edition (ASQ-3). The PDMS-2 was used to evaluate gross motor development function before PICU discharge. Results The gross motor developmental dysfunction incidence was 68.6%. Linear correlation analysis showed that the gross motor quotient (GMQ) was positively correlated with the pediatric critical illness score (PCIS, r = 0.621, P < 0.001), and negatively correlated with length of PICU stay (r = − 0.556, P = 0.001), days sedated (r = − 0.602, P < 0.001), days on invasive mechanical ventilation (IMV; r = − 0.686, P < 0.001), and days on continuous renal replacement therapy (CRRT; r = − 0.538, P = 0.001). Linear regression analysis showed that IMV days (β = − 0.736, P = 0.001), sepsis (β = − 18.111, P = 0.003) and PCIS (β = 0.550, P = 0.021) were independent risk factors for gross motor developmental dysfunction. Conclusions Gross motor developmental dysfunction in infantile and toddler PICU survivors is more common and may be exacerbated by experiences associated with longer IMV days and increasing illness severity combined with sepsis. Trial registration The trial 'Early rehabilitation intervention for critically ill children' has been registered at http://www.chictr.org.cn/showproj.aspx?proj=23132. Registration number: ChiCTR1800020196.